2023
DOI: 10.1007/s13555-023-00913-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Risankizumab for the Treatment of Hidradenitis Suppurativa: A Phase 2, Randomized, Placebo-Controlled Trial

Abstract: Introduction: Hidradenitis suppurativa (HS) is a chronic, immune-mediated skin condition characterized by inflammatory lesions that can cause pain, impaired physical activity, and reduced quality of life. This study evaluated the efficacy and safety of risankizumab, a humanized immunoglobulin G1 monoclonal antibody that specifically inhibits interleukin 23 by binding to its p19 subunit, for the treatment of HS. Methods: This phase II multicenter, randomized, placebo-controlled, double-blind study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Risankizumab is a humanized monoclonal antibody that inhibits IL-23p19. A phase 2 trial in 243 participants evaluated two dosing regimens of risankizumab compared with placebo [ 111 ]. The study was terminated early, as the primary endpoint was not met: 46.8% of patients in the risankizumab 180 mg group, 43.4% of the risankizumab 360 mg group, and 41.5% of the placebo group achieved HiSCR at week 16.…”
Section: Resultsmentioning
confidence: 99%
“…Risankizumab is a humanized monoclonal antibody that inhibits IL-23p19. A phase 2 trial in 243 participants evaluated two dosing regimens of risankizumab compared with placebo [ 111 ]. The study was terminated early, as the primary endpoint was not met: 46.8% of patients in the risankizumab 180 mg group, 43.4% of the risankizumab 360 mg group, and 41.5% of the placebo group achieved HiSCR at week 16.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results from two phase III trials have demonstrated sustained efficacy and safety of secukinumab on HS for up to 52 weeks of treatment, when given every 2 weeks [16]. On the contrary, phase II studies did not provide strong evidence to support the efficacy of IL-23 inhibitors on HS, putting into question the central role of the IL-23/T-helper 17 axis in HS pathophysiology [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…HiSCR was achieved by 46.8%, 43.4%, and 41.5% at week 16, respectively, indicating that risankizumab does not appear to be an effective treatment for moderate-to-severe HS [98].…”
Section: Anti-il-12/23 Therapy and Anti-il-23 Therapymentioning
confidence: 92%
“…A phase II trial allocated patients randomly to receive risankizumab 180 mg, risankizumab 360 mg, or placebo subcutaneously. HiSCR was achieved by 46.8%, 43.4%, and 41.5% at week 16, respectively, indicating that risankizumab does not appear to be an effective treatment for moderate-to-severe HS [98].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 92%